2022
DOI: 10.1177/20552076221102253
|View full text |Cite
|
Sign up to set email alerts
|

Canadian perspectives of digital mental health supports: Findings from a national survey conducted during the COVID-19 pandemic

Abstract: Objectives The impact of the COVID-19 pandemic on population mental health has highlighted the potential for digital mental health to support the needs of those requiring care. This study sought to understand the digital mental health experiences and priorities of Canadians affected by mental health conditions (i.e. seekers, patients, and care partners). Methods A national cross-sectional electronic survey of Canadians was administered through a market research firm's survey panel. Seekers, patients, and care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…1 The COVID-19 crisis is a catalyst for population mental health problems. 2 As highlighted by UNICEF for Latin America and the Caribbean, 27% and 15% of the youths suffered from anxiety feeling and depression, respectively. 3 Patients in the United States (18.1%) were also given a psychiatric diagnosis, such as anxiety, depression, or insomnia within 3 months of receiving a COVID-19 diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…1 The COVID-19 crisis is a catalyst for population mental health problems. 2 As highlighted by UNICEF for Latin America and the Caribbean, 27% and 15% of the youths suffered from anxiety feeling and depression, respectively. 3 Patients in the United States (18.1%) were also given a psychiatric diagnosis, such as anxiety, depression, or insomnia within 3 months of receiving a COVID-19 diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to a 2021 pan Canadian survey, approximately 70% of respondents reported using a digital health tool to support their mental health in the past year [15]. Moreover, approximately one third of respondents were satis ed with the digital mental health tools available to them [15]. Unsurprisingly, other studies have found that those with increased rates of depressive and anxiety symptoms are more likely to use digital mental health tools [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, those seeking mental health care supports, sometimes turned to consumer digital health tools such as web-based courses or platforms, mobile health apps, chatbots, and phone or text-based supports [14]. According to a 2021 pan Canadian survey, approximately 70% of respondents reported using a digital health tool to support their mental health in the past year [15]. Moreover, approximately one third of respondents were satis ed with the digital mental health tools available to them [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations